LEGAL FRAMEWORK CONCERNING RENEWABLE ENERGY IN SUSTAINING INDONESIA'S HALAL INDUSTRY - Muthia Sakti; Imam Haryanto; Dwi Aryanti Ramadhani; Sulastri (Institut Pendidikan Indonesia, 2023)
This article intends to describe the function of new and renewable energy in assisting the halal sector in Indonesia by using descriptive and comparative analytical studies on initiatives carried out by Germany about new and renewable energy. Indonesia has a very high potential to develop into a global powerhouse for halal food because its population is predominately Muslim. To accomplish this goal, the halal industry needs cooperation from various areas, one of which is innovative and renewable energy. However, Indonesia's inconsistent rules, particularly those governing investment, impede the development of new renewable energy sources. Investors must grow the initial business of renewable energy because it has high costs but can reduce the consumption of electricity or fossil fuels. Following that, this new renewable energy will be applied to various other industries, including halal food and beverages, pharmaceuticals and cosmetics, fashion, and tourism. The geographic position of Indonesia is another aspect that encourages the development of new renewable energy sources.